Development of Booklets Integrated with Islamic Values Based on Socio-Scientific Issues to Improve Science Literacy - Afriandi, Muhammad; Widiyatmoko, Arif; Astuti, Budi (Journal of Natural Science and Integration, 2025)
One of the persistent challenges in education is the lack of innovation in teaching materials. Conventional textbooks often fail to connect scientific content with real-world environmental issues, contributing to students’ low levels of scientific literacy. This study aims to evaluate the feasibility and effectiveness of a socio-scientific issue (SSI)-based booklet integrated with Islamic values in enhancing students’ scientific literacy. Utilizing the Borg & Gall research and development model, the study employed purposive sampling involving 33 students from class VIIF at MTs Nurul Huda Tarub. Data were collected through questionnaires and literacy tests. Expert validation and effectiveness analyses were conducted using expert judgment and paired sample t-tests, respectively. The booklet received high validation scores: 96% from material experts, 97% from media experts, 97% from educators for practicality, and 98% from student evaluations. The paired sample t-test yielded a significance value of 0.000, indicating a statistically significant improvement in scientific literacy post-intervention. The findings affirm that the developed booklet is highly valid and effective in promoting students' scientific literacy. This suggests that embedding Islamic values within SSI-based learning materials can foster more contextual, meaningful, and character-building science education, supporting the holistic development of students’ scientific reasoning and religious awarenessKeywords: booklet, integrated islamic values, scientific literacy.